Long Coronary Lesions Treated With Thin Strut Bioresorbable Polymer Drug Eluting Stent: Experience From Multicentre Randomized CENTURY II Study. (February 2016) - Lesiak, Maciej; Araszkiewicz, Aleksander; Grajek, Stefan; Colombo, Antonio; Lalmand, Jacques; Carstensen, Steen; Namiki, Atsuo; Tobaru, Tetsuya; Merkely, Béla; Moreno, Raul; Barbato, Emanuele; Wijns, William; et al.
Abstract : Objectives: to assess performance of new, bioresorbable polymer sirolimus‐eluting stent (BP‐SES), in patients with long coronary lesions (LL) and to compare it to permanent polymer everolimus‐eluting stent (PP‐EES). Background: LL have been associated with worse clinical outcomes in percutaneous coronary interventions (PCI). The impact of lesion length on the outcomes of drug eluting stent (DES) implantations is not as clear. Methods: In the frame of a randomized, multicentre CENTURY II study, out of 1119 patients enrolled, 182 patients had LL (defined as ≥25 mm), and were assigned randomly to treatment with BP‐SES (101) or PP‐EES (81). Primary endpoint was target lesion failure (TLF, composite of cardiac death, target vessel related myocardial infarction [MI], and target lesion revascularization [TLR]) at 9 months. All data were 100% monitored and adverse events were adjudicated by an independent clinical event committee. Results: The baseline patient and lesion characteristics were similar in the 2 study arms. At 9‐months, the rates of cardiac death (2.0% vs 1.2%; P = 0.70), MI (3.0% vs 4.9%; P = 0.49) and clinically driven TLR (2.0% vs 3.7%; P = 0.48) and TLF (6.9% vs 8.6%; P = 0.67) were similar for BP‐SES and PP‐EES, respectively. There was no stent thrombosis (ST) in BP‐SES group up to 9 months, while 1 case (1.2%) of ST was recorded in PP‐EES group (P = 0.44). Conclusions: Patients with LL showed similar clinical outcomes when treated with Ultimaster BP‐SES and Xience PP‐EES. (J Interven Cardiol 2016;29:47–56)